VALUABLE ASPECTS OF IMPLEMENTATION OF DIGITAL TRANSFORMATION IN TO THE ECONOMY - Shakhnoza Ashurova (Scholar Express Journals, 2023)
In this article we can observe the valuable aspects of implementation of digital transformation as well as in economy, effectiveness in all spheres of life occur and also the transition to the digital economy will certainly not affect the increase in production efficiency, the increase in the competitiveness of companies, the reduction of production costs, the creation of new jobs, and the emergence of new modern professions. In short, the development of the digital economy can change our lives in a positive way. The purpose of the study is to shed light on the nature of the digital economy, identify its advantages and disadvantages, and develop scientific proposals and practical recommendations for further development of this field in Uzbekistan
Keywords: digital; transformation; economy